Prevención de Caídas: Como Manejar una Caída - Linda B. Bobroff; Leigh Ann Martin (EDIS)
Revised! FCS2233-Span, a 1-page fact sheet by Linda Bobroff and Leigh Ann Martin, is the Spanish Language version of "Fall Prevention: How to Handle a Fall." It gives steps to follow to decrease the chance of further injury after a fall, including line drawings showing how to pull oneself onto a chair. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, May 2006.